2023
DOI: 10.4018/978-1-6684-6408-3.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Smart City Approaches Using Machine Learning and the IoT

Abstract: Machine learning has attracted the interest of academics and industrialists and is likely to develop. Machine learning may deliver widespread wireless connectivity. Machine learning enables the internet of things (IoT), which allows objects to communicate without human intervention. Healthcare, smart grids, vehicular communications, etc. use machine learning. The authors explore IoT-based machine learning methods applied in these sectors and others. Lessons learnt and judgments of machine learning's use in IoT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Facial expression analysis is one of the most widely studied areas in computer vision-based systems for the SHH [13]- [16]. It has been shown that facial expressions are reliable indicators of emotional changes and can provide valuable information about the patient's mental state [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Facial expression analysis is one of the most widely studied areas in computer vision-based systems for the SHH [13]- [16]. It has been shown that facial expressions are reliable indicators of emotional changes and can provide valuable information about the patient's mental state [17], [18].…”
Section: Introductionmentioning
confidence: 99%